Penerapan Metode Qiraati dalam Meningkatkan Kemampuan Membaca Al-Qur’an Santri di TPQ Azzahra Kabupaten Probolinggo - Nur Lailatul Hikmah; Nazahah Ulin Nuha (Education Reserach Center, 2025)
This study aims to examine the application of the Qiraati method in improving Qur’anic reading skills among students at TPQ Azzahra, Probolinggo Regency. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation. The findings reveal that the Qiraati method is implemented through a structured jilid-based system, encouraging reading without spelling and applying direct tashih to correct errors in makhraj and tajwid. Students showed positive responses and notable progress at each level. Key success factors include experienced instructors, complete instructional materials, and a supportive learning environment. Challenges include disparities in students’ initial abilities, limited practice at home, and inconsistent teaching approaches. Overall, the Qiraati method is effective in enhancing Qur’anic literacy, though improvements in study habits and classroom management are recommended to optimize outcomes.